Advances in Contact Angle, Wettability and Adhesion 2013
DOI: 10.1002/9781118795620.ch3
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Nucleation on a Completely Wettable Substrate

Abstract: It is widely believed that heterogeneous nucleation occurs without an activation process when the surface is completely wettable. In this report, we review our previous work [J.Chem.Phys 134, 234709 (2011)] to show that the critical nucleus (droplet) can exist and the activation process may be observable. In fact, a critical nucleus and a free energy barrier always exist if the surface potential or the disjoining pressure allows for the firstorder pre-wetting transition on a completely wettable substrate where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 48 publications
(112 reference statements)
0
6
0
Order By: Relevance
“…Equation predicts that the formation of the critical nucleus is barrierless beyond that limit (region of complete wetting by ice in Figure ). On approaching this limit, the line tension of the ice–liquid–surface line, neglected in eq , would make an important contribution to the free energy barrier of nucleation and should be included in the CNT formulation. , Moreover, Iwamatsu has demonstrated that the existence of prewetting transitions leads to break down of CNT on approaching the complete wetting by ice limit, which results in a finite nucleation barrier for the heterogeneous nucleation of liquid from vapor . The conclusions of ref have not yet been generalized for the nucleation of a crystalline nucleus on a soft, wavy surface; but they would suggest that for surfaces with Δ G bind ≤ −2γ ice–water the freezing temperature approaches the equilibrium melting line but a finite barrier could still exist for heterogeneous nucleation.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Equation predicts that the formation of the critical nucleus is barrierless beyond that limit (region of complete wetting by ice in Figure ). On approaching this limit, the line tension of the ice–liquid–surface line, neglected in eq , would make an important contribution to the free energy barrier of nucleation and should be included in the CNT formulation. , Moreover, Iwamatsu has demonstrated that the existence of prewetting transitions leads to break down of CNT on approaching the complete wetting by ice limit, which results in a finite nucleation barrier for the heterogeneous nucleation of liquid from vapor . The conclusions of ref have not yet been generalized for the nucleation of a crystalline nucleus on a soft, wavy surface; but they would suggest that for surfaces with Δ G bind ≤ −2γ ice–water the freezing temperature approaches the equilibrium melting line but a finite barrier could still exist for heterogeneous nucleation.…”
Section: Results and Discussionmentioning
confidence: 99%
“…However, it is possible to include long-ranged liquid-solid interaction by using the concept of disjoining pressure. Several studies 20,[44][45][46] have already examined the effect of the long-range force. However, most of those studies have focused on the case of complete wetting with the contact angle θ = 0…”
Section: Discussionmentioning
confidence: 99%
“…Heterogeneous nucleation occurs when the binding free energy of the crystal (immersed in its melt) to the nucleating surface is negative (∆G bind < 0), while surface freezing requires a more stringent condition: that the binding free energy is less than minus twice the liquid-crystal surface tension of the alkane, (∆G bind < −2 γ xl ) [13,109]. This implies that there is a range of binding free energies for which heterogeneous nucleation can occur without surface freezing.…”
Section: Discussionmentioning
confidence: 99%
“…Heterogeneous nucleation can only be induced when cosα > −1, which implies that the binding free energy of the crystal nucleus to the surface is negative, ∆G bind = γ xs − (γ ls + γ xl ) < 0 ( Figure 6) [13]. Surface freezing can be considered a case of complete wetting of the surface by the crystal, which requires that ∆G bind < −2 γ xl ( Figure 6) if the line tension of the crystal-liquid-surface interface is neglected [13,109]. Heterogeneous nucleation at a surface can occur without surface freezing when −2 γ xl < ∆G bind < 0.…”
Section: The Sign and Magnitude Of The Binding Free Energy Of The Alkmentioning
confidence: 99%
See 1 more Smart Citation